La capacitación de Neurociencia y el mejoramiento del aprendizaje de los estudiantes del nivel inicial de la I.E.A.C, Virgen de la Puerta 2017 - Adrianzén Fernández, Jovita del Rocío (2018)
ABSTRACT The purpose of this research study is to determine whether Neuroscience training given to teachers in public educational institutions improves the learning of students at the initial level of the I.E.A.C. "Virgen de la Puerta" 2017, being necessary to know the level of learning of the students of the initial level, of the I.E.A.C. "Virgen de la Puerta" 2017, before and after the teachers apply the knowledge acquired from the Neuroscience training, in the areas of mathematics, communication and psychomotricity, it is worth mentioning that to carry out this study, there was a population made up of students of the initial level of 5 years of the section "A" (25, between boys and girls) and the section "B" (25, between boys and girls), being a total of 50, the same one that was used as sample size defined in two experimental and control groups, it is also important that the methodology to be used in the present work was a pre - experimental design, with a correlational descriptive approach, for two groups since, it was necessary to know the effect or reaction that would result from the Teachers who attended the neuroscience training applied the teaching with the students of the "A" section. On the other hand, as a result, the average score obtained by the 5-year-old students "A" from the initial level in terms of their answers in the test that was initially applied was at a bad level (mean = 1.08,), but after receiving the class by the teachers who attended the training, the average of their scores turned out to be at a regular level their learning (average = 1.76,), almost in the areas of mathematics, communication and psychomotricity while for the group control was always in the same result. Therefore, it was determined that the training of Neuroscience given to teachers of public educational institutions, significantly improved the learning of the students of the initial level, of the I.E.A.C. "Virgin of the Door" 2017.